Nitrogen compunds in the surface water identifying concentrations and sources - Bradulienė, Jolita; Grubliauskas, Raimondas (International Conference “Environmental Engineering”, 2017)
The main objective of the surface water monitoring – periodically to conduct water quality testing, to find out the possible sources of pollution in time and to warn population. Water samples for analysis of surface water bodies – rivers Raseika (Raseiniai district, central Lithuania) were taken during the autumn season. The river Raseika belongs to the basin of the river Jura. This river was drained for many times and has a lot of ponds. The treated urban sewage of Raseiniai wastewater treatment plants flows to this river. Also the river Raseika is polluted by population sewage, which are not collected and treated. The river Raseika flows through Dubysa Regional Park area, which was established in 1992 to preserve Dubysa erosive valley landscape, natural and cultural heritage values: the picturesque Dubysa valley; significant geomorphological, hydrographic, cultural, botanical and landscape values, natural ecosystem stability, biota components, unique flora and fauna, natural fish migration routes and spawning grounds. Six points were selected to carry out the monitoring of the river Raseika. The nitrogen concentrations were mostly not corre sponding to the standards. Most of the ascendances were found in samples where the treated urban sewage of Raseiniai city wastewater treatment plants flows in the river.